• TH1: $x+y+z \ne 0$
Ta có: $ \dfrac{x+y-z}{z}=\dfrac{y+z-x}{x}=\dfrac{z+x-y}{y}=\dfrac{x+y-z+y+z-x+z+x-y}{x+y+z}=\dfrac{x+y+z}{x+y+z}=1$
$\Longrightarrow \dfrac{x+y-z}{z}=1 \Longrightarrow x+y-z=z \Longrightarrow x+y=2z$
Tương tự, ta có: $y+z=2x; z+x=2y$
$ P= (1+\dfrac{y}{x})(1+\dfrac{z}{y})(1+\dfrac{x}{z})$
$=\dfrac{x+y}{x}.\dfrac{y+z}{y}. \dfrac{z+x}{z}=\dfrac{2z.2z.2y}{xyz}=8$
• TH2: $x+y+z=0 \Longrightarrow x+y=-z; y+z=-x; z+x=-y$
$P= P= (1+\dfrac{y}{x})(1+\dfrac{z}{y})(1+\dfrac{x}{z})$
$=\dfrac{x+y}{x}.\dfrac{y+z}{y}. \dfrac{z+x}{z}=\dfrac{-xyz}{xyz}=-1$